Direct observation of the influence of the FeAs4 tetrahedron on superconductivity and antiferromagnetic correlations in Sr2VO 3FeAs - Garbarino, Gastón (2011)
We measure the pressure dependence of the electrical resistivity and the crystal structure of iron superconductor Sr2VO3FeAs. Below ∼10 GPa the structure compresses but remains undeformed, with regular FeAs4 tetrahedrons, and a constant Tc. Beyond 10 GPa, the tetrahedron strongly distorts, while Tc goes gradually to zero. Band structure calculations of the undistorted structure show multiple-nesting features that hinder the development of an antiferromagnetic (AF) ground state, allowing the appearance of superconductivity. The deformation of the tetrahedra that breaks band degeneracy degrades multiple nesting, thus favouring one particular AF state at the expense of Tc.